ANALISIS KEMAMPUAN PEMBUKTIAN MATEMATIS PADA MATA KULIAH TEORI RING DITINJAU DARI PENDIDIKAN SEKOLAH MENENGAH - Nina Agustyaningrum; Paskalia Pradanti; Dita Aldila Krisma (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Mathematical proof is a crucial component in studying mathematics, especially at advanced levels. Previous research has reported that many students face difficulties in solving mathematical proof problems, including in rings theory course. This study aims to determine the level of students' mathematical proof abilities in ring theory course and to compare these abilities based on their school backgrounds. This research employs a quantitative descriptive approach followed by comparative analysis. The subjects were 30 students from the mathematics education program taking rings theory course at Tidar University. The research instruments include tests, questionnaire, and interviews guidelines. Data analysis of the test results was conducted using descriptive statistic and one-way ANOVA followed by Tukey HSD post hoc tests. The research findings indicate that students' overall mathematical proof abilities fall into the low category, with an average score of 41.67 (on a scale of 100). From these results, 84% of the respondents are in the low category, 13% in the medium category, and 3% in the high category. Furthermore, when considering the backgrounds of secondary schools MA, SMK, and SMA, the average scores for mathematical proof abilities in all three groups are in the low category. The one-way ANOVA and Tukey HSD post hoc tests reveal a significant difference in mathematical proof abilities between the MA and SMA groups, while there was no significant difference between the MA and SMK groups or the SMK and SMA groups